IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEMS IN CONSTRUCTION PROJECTS IN TIMOR-LESTE - A Koesmargono; Yuniati J Mendes (Universitas Medan Area, 2023)
Infrastructure development is one of the priorities to help turn the economy in Timor Leste, especially the construction of buildings, paving roads, airfields and other structures. In general, the process of building a construction project is an activity that contains an element of danger. Therefore, an Occupational Safety and Health Management System in the construction industry is needed. The research was carried out by identifying the causes and potential for accidents to occur in each project implementation. From the data taken from IGT from 2010-2020, 18 cases were recorded, namely 14 cases of death, 1 person was slightly injured and 2 people were injured. Therefore, a company engaged in construction work must have an Occupational Health and Safety management system, to reduce the occurrence of accidents in the workplace. The method used in collecting data in this study is descriptive analysis method. That is by directly visiting seven (7) ongoing construction projects, to conduct interviews and direct observations regarding the Implementation of the Occupational Safety and Health Program and to distribute Questionnaires. The results of distributing the questionnaires were 31 respondents, and the results of interviews and observations made by researchers, it was found that of the seven projects, only two (2) projects implemented the K3 System in the company, and the company itself did not care about and meet the needs in helping work in Work.